P/E RATIO DALAM VALUASI SAHAM UNTUK PENGAMBILAN KEPUTUSAN INVESTASI (Studi Kasus Saham Emiten Yang Terdaftar Pada Jakarta Islamic Index Periode 2018) - Dhistianti Mei Rahmawantari; Ayu Puspitaningtyas (Jurnal Ekonomi dan Industri, 2019)
Stock valuation is a valuation tool to knows the fair price or intrinsic value of a stock, so it can be used to predict potential losses and profits to be received by investors, the method used in this study is to use the P / E ratio or PER. ROE, DPS and EPS are important components that are used to calculate intrinsic value in this study. Using financial statement data from a total of 26 companies that distributed dividends and joined the Jakarta Islamic Index (JII) during the 2018 period, this study found that there were 12 companies included in the undervalue category and 14 companies included in the overvalued category. From total of the 12 companies that are categorized as undervalued, there are 5 companies that have a small PER value. The use of the P / E ratio method in this study can be used as an alternative method that is well used in investment decision making by investors.